Habitats of Kolkheti lowland, ecotourism and recreational potential - Matchutadze, Izolda; Goradze, Rezo; Tetemadze, Natela; Cheishvili, Tamar; Bagrationi, Guranda ("Intercultural Dialogues" Transactions, 2023)
There are 36 critical hotspots of biodiversity in the world (Conservation International). The Caucasus hotspot, which spans 532,658 km² is one of them. Consequently, Georgia with the admired Kolkheti lowland surrounded by the Greater and Lesser Caucasus Ranges belongs to this hotspot region. Because of its climatic and geographic situation, the Kolkheti lowland represents a centre of biodiversity and human activity on the transition of Europe and Asia. The main habitats in the Kolkheti lowland are the relict Kolkheti relict forests, the peatlands, the wetlands, coastal sand zones, river mouths, open fresh and salt water areas. The main habitats in the Kolkheti lowland are the relict Kolkheti forests, the peatlands, the wetlands, coastal sand zones, river mouths, open fresh and salt water areas. Habitats of Kolkheti lowland such as: Relict Forest and Sphagnum m ire are under the UNESCO WNH nomination since 2021 (Feasibility…2019). Tourist and recreational potential. The tourist and recreational potential of the territory is determined by the attractive natural environment: rivers, wildlife and seascapes, peatlands, migratory birds, rich historical and cultural values. The protected area has the potential to develop a variety of tourist products. These are: boating, fishing (amateur fishing), bird watching tourism, cultural-historical, educational, scientific-research and rural tourism.